Advances in endodontics: Potential applications in clinical practice - Kishen, Anil (J Conserv Dent, 2016)
Contemporary endodontics has seen an unprecedented advance in technology and materials. This article aimed to review some of the challenges and advances in the following sections: (1) endodontic imaging, (2) root canal preparation, (3) root canal disinfection, (4) root canal filling, and (4) regenerative endodontic procedures (REPs). Jointly, these advances are aimed at improving the state of the art and science of root canal treatment.